NiFe2O4/poly(ethylene glycol)/lipid–polymer hybrid nanoparticles for anti-cancer drug delivery. (16th October 2020) - Joshy, K. S.; Augustine, Robin; Mayeen, Anshida; Alex, Susan M.; Hasan, Anwarul; Thomas, Sabu; Chi, Hong
Abstract : The present study reports the fabrication of hybrid nanoparticles consisting of nickel ferrite (NFO) for anti cancer drug delivery. Abstract : The present study reports the fabrication of hybrid nanoparticles consisting of nickel ferrite (NFO) for anti cancer drug delivery. The hybrid system was formulated from poly(vinyl alcohol)/stearic acid with PEG containing nickel ferrite for zidovudine (AZT) delivery. The nickel ferrite nanoparticles were characterized by XRD and TEM analysis. The hybrid nanoparticles were characterized by dynamic light scattering (DLS) and transmission electron microscopy (TEM), and their influence on biological systems was evaluated by blood compatibility and cell viability studies. The encapsulation of AZT into the hybrid nanoparticles was assessed by evaluating the drug loading, encapsulation efficiency and release studies. The advantages of incorporating magnetic nanoparticles into self-assembled hybrid nanoparticles include the ability to load large amounts of drugs along with control over drug release. In this regard, the presented nickel ferrite reinforced hybrid nanoparticles containing zidovudine is a demanding platform that can act in a pH responsive manner enabling site specific intracellular anticancer drug delivery. Its impact is therefore noteworthy, extensive, and prevalent in cancer therapy.